Multiple burr hole and erythropoietin combination therapy: optimal early surgical intervention for patients with acute stroke episode of moyamoya disease or moyamoya syndrome - Lee, Yeonhu; Lee, Jin Soo; Lee, Seong-Joon; Hong, Ji Man; Lim, Yong Cheol (Frontiers in Neurology, 2024)
ObjectiveThe optimal timing of bypass surgery for patients with moyamoya disease (MMD) or moyamoya syndrome (MMS) following an acute stroke episode remains unclear, mainly owing to the risk of postoperative complications. In this study, we aim to validate the safety and efficacy of early intervention using multiple burr hole (MBH) and erythropoietin (EPO) therapy, thereby refining the management strategy for patients with acute stroke episode of MMD or MMS.MethodsWe retrospectively analyzed data from 70 patients with MMD or MMS who underwent MBH and EPO therapy. The cohort was divided based on the time interval between the latest neurological deterioration and surgery: early (<30 days) and later (≥30 days) groups. We evaluated and compared perioperative clinical parameters and the extent of neovascularization on a 6-month postoperative angiography. Long-term clinical outcomes, including transient ischemic attack (TIA), infarction, hemorrhage, and seizure, were also analyzed during the follow-up period.ResultsIn the cohort, 36 patients (51.4%) were in the early group, whereas 34 (48.6%) were in the later group. The 6-month follow-up angiography demonstrated that 34/47 hemispheres (72.3%) in the early group exhibited successful neovascularization (≥2/3 of MCA territories) compared with the 19/44 (43.2%) hemispheres in the later group (odds ratio [OR] = 3.44; 95% confidence interval [CI]: 1.46–8.45; p < 0.01). In addition, a notable reduction (≥50%) in basal moyamoya vessels was observed in 30/47 hemispheres (63.8%) from the early group vs. 12/44 (27.3%) hemispheres from the later group (OR = 4.71; 95% CI: 1.97–11.82; p < 0.001). During the average follow-up of 56.5 months, only six patients experienced infarction or hemorrhage.ConclusionOur dataset suggests that MBH and EPO combination therapy is an effective, minimally invasive, and acceptable treatment, even in the early period of patients with MMD or MMS following an acute stroke episode.